Content Validation of the Operational Definitions of the Nursing Diagnoses of Activity Intolerance, Excess Fluid Volume, and Decreased Cardiac Output in Patients With Heart Failure - Souza, Vanessa de; Zeitoun, Sandra Salloum [UNESP]; Lopes, Camila Takao; Dias de Oliveira, Ana Paula; Lopes, Juliana de Lima; Botura Leite de Barros, Alba Lucia (Wiley-Blackwell, 2014)
Objectives To consensually validate the operational definitions of the nursing diagnoses activity intolerance, excessive fluid volume, and decreased cardiac output in patients with decompensated heart failure. Method Consensual validation was performed in two stages: analogy by similarity of defining characteristics, and development of operational definitions and validation with experts. Results A total of 38 defining characteristics were found. Operational definitions were developed and content-validated. One hundred percent of agreement was achieved among the seven experts after five rounds. Ascites was added in the nursing diagnosis excessive fluid volume. Conclusion The consensual validation improves interpretation of human response, grounding the selection of nursing interventions and contributing to improved nursing outcomes. Implications for Practice Support the assessment of patients with decompensated heart failure. Objetivos Realizar a validacAo consensual das definicoes operacionais dos diagnosticos de enfermagem Intolerancia a atividade, Volume de liquidos excessivo e Debito cardiaco diminuido em pacientes com insuficiencia cardiaca descompensada. Metodo ValidacAo consensual em duas etapas: Analogia de semelhanca das caracteristicas definidoras e desenvolvimento de definicoes operacionais e validacAo com expertst. Resultados Foram encontradas 38 caracteristicas definidoras para os diagnosticos de enfermagem. Suas definicoes operacionais foram desenvolvidas e seu conteudo validado. Os resultados mostram que houve 100% de concordancia entre os sete experts apos cinco rodada. As definicoes operacionais foram classificadas com base no nivel de concordanica. Ascite foi acrescentada ao diagnostico Volume de liquidos excessivo. ConclusAo A validacAo consensual melhora a interpretacAo das respostas humanas, embasando a selecAo de intervencoes de enfermagem e contribuindo para melhorar os resultados. Implicacoes Para A Pratica Apoio a avaliacAo dos pacientes com insuficiencia cardiaca descompensada.
Keywords: Heart failure; nursing diagnosis; validation study